(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Life according to Ayurveda is considered as the Samyoga (combination) of Sarira (body), Indriya (sense organs), Satwa (mind) and Atma (soul). Among them Indriya refers to Arishta according to Charaka. Indriya Sthana states the relevance and importance of knowing Aristhta lakshanas before going to treatment. Arishta means, it is the state in which it has transcended all the remedial measures and widespread all over the body by the aggravation of Tridoshas. It is important in prognostication process, to prognosticate remaining survival time, in proper clinical decision making, to analyze the role and potential of Arishta Lakshanas in contemporary clinical prognostication, it helps to decide which patient to treat and which not to treat, whom to give palliative treatment and whom to give intervention treatment and helps to approach death with understanding and ease. Objective: To document perceptions, observations and experiences of nurses working in critical care on manifestation of Arishta Lakshanas in dying patients. Method: Survey study (77 nurses from different hospitals in state, national and international level was contacted and an online survey via Google forms was conducted). Results: Some of the changes in the parameters have been observed by the nurses in dying patients. Conclusion: Without Arishta Lakshanas no death occurs. So here an effort has been made to document the Arishta Lakshanas based upon some factors among the forty-eight examination factors of Aayu or Arishta stated in Indriya Sthana.